Compartmental and Non-Compartmental Pharmacokinetic Analysis of Extended Release Diclofenac Sodium Tablet - Qusai, Uns; Hameed, Asma; Rasheed, Khawla Hameed (Nahrain University College of Engineering Journal, 2017)
Compartmental modeling describes themovement of a substance from one compartment to another. it is concerned with maintaining correct chemical levels in the body and their correct fluid volumes. From another side non compartmental analysis have many benefits over compartmental analysis like it requires less experience and skill on the part of the modeler, in-vivo study made on seven healthy volunteers, plasma concentration versus time obtained then both compartmental and non compartmental analysis applied to data, the clearance, volume of distribution, half life, and area under the curve from zero to infinity were comparable to each other for tow methods, The correlation between observed and predicted plasma concentration versus time profiles using compartmental analysis was 0.95.